Harmonisasi Prinsip Hukum Islam dan Hukum Positif dalam Perjanjian Waralaba di Indonesia: Kajian Keadilan dan Kepastian Hukum - Zulkifli, Suhaila; Noor, Tajuddin; Pakpahan, Marlina Elisabeth (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Franchise agreements have become a prevalent business model in Indonesia, facilitating entrepreneurial opportunities and driving economic growth. However, the inherent power imbalance between franchisors and franchisees often leads to conflicts that challenge the principles of justice and fairness. This research aims to explore the harmonization of Islamic law (Sharia) and positive law principles in regulating franchise agreements in Indonesia. By adopting a qualitative approach, the research examines the convergence and divergence between these two legal frameworks, with a focus on upholding the ethical tenets of Islamic business practices, such as justice, honesty, and trust. The findings highlight the importance of developing a comprehensive legal framework that balances the interests of both franchisors and franchisees, ensures transparent dispute resolution mechanisms, and promotes the equitable distribution of rights and obligations. This study contributes to the ongoing discourse on the integration of religious and secular legal principles in the context of franchise relationships, providing practical insights for policymakers, legal practitioners, and industry stakeholders to foster a more harmonious and sustainable franchise ecosystem in Indonesia.